Investigação da ação central do timol em modelos comportamentais de ansiedade, depressão e convulsão em camundongos - Fernandes, Mariana Lima (2012)
Thymol (2-isopropyl-5-methyl-phenol) an isomer of Carvacrol. Present as large colorless crystals or white crystalline powder. It is a monoterpene essential oil extracted from various herbs, and the main component of the essential oil of rosemary-pepper (Lippia sidoides), constituting approximately 48% of its composition. This paper presents the behavioral actions of thymol in animal models of anxiety, depression, seizures and sedation, such as elevated plus maze (EPM), open field, rota rod, forced swim, tail suspension, seizure induced by pentylenetetrazol and pentobarbital-induced sleep time. Thymol was administered orally in male mice at doses of 25mg/kg and 50mg / kg. The results showed that thymol at both doses studied did cause muscula relaxament activits change locomotor activity on the test rota rod nor the number of crossings in the open field test, but reducedThe grooming was reduced with the administration of thymol in the open field test. At both doses studied LCE thymol increased all parameters observed suggesting a possible anxiolytic effect. Flumazenil, an antagonist of GABA / benzodiazepine, reversed this effect. In the test of sleep time induced by pentobarbital thymol not alter the latency but increased sleep duration. Although this test is sensitive to CNS depressant agents but is not specific for compounds which would interfere with the biotransformation of pentobarbital. In the test of pentylenetetrazol-induced seizures, thymol increased latency of seizure at the dose of 50mg/kg, however was not able to change the mortality of animals. Thymol showed antidepressant effect in the forced swim test and the tail suspension. This effect was reversed by pretreatment of animals with PCPA (a serotonin synthesis inhibitor), Prazosin and Yohimbine (adrenoreceptor antagonists), SCH23390 and Sulpiride (dopamine receptor antagonists). These results suggest that thymol shows anxiolytic effects probably associated with the GABAergic system and antidepressant effects associated with the serotonergic, noradrenergic and dopaminergic without causing sedation.